Treatment needs, diagnoses and use of services for acutely admitted psychiatric patients in northwest Russia and northern Norway - Sørgaard, Knut; Rezvyy, Grigory; Bugdanov, Anatoly; Sørlie, Tore; Bratlid, Trond (International Journal of Mental Health Systems, 2013)
Background: We compared demography, diagnoses and clinical needs in acutely admitted psychiatric hospital patients in northwest Russia and northern Norway. Method: All acutely admitted psychiatric patients in 1 psychiatric hospital in north-west Russia and 2 in northern Norway were in a three months period assessed with HoNOS and a Norwegian form developed to study acute psychiatric services (MAP). Data from a total of 841 patients were analysed (377 Norwegian, 464 Russian) with univariate and multivariate statistics. Results: Russian patients were more often males who had paid work. 2/3 were diagnosed with alcohol and organic disorders, and 70% reported problems related to sleep. Depression was widespread, as were problems associated with occupation. Many more Norwegian patients were on various forms of social security and lived in community supported homes. They had a clinical profile of affective disorders, use of drugs, suicidality and problems with activities involved of daily life. Slightly more Norwegian patients were involuntary admitted. Conclusion: Acutely admitted psychiatric patients in North West Russia and Northern Norwegian showed different clinical profiles: alcohol, depression and organic disorders characterised Russian patients, affective disorders, suicidality and use of drugs characterised the Norwegians. Whereas Norwegian patients are mainly referred from GPs the Russians come via 1.line psychiatric services (“dispensaries”). Average length of stay for Russian patients was 2.5 times longer than that of the Norwegian.